INQUISITION ON COALESCE STRATEGIES IN PREVENTION OF PRE-ECLAMPSIA, MATERNAL, FETAL & NEONATAL OUTCOME: A RANDOMISED CLINICAL TRIAL - PROF. K.LATHA; DR.PROF.A.JUDIE (International Journal of Pharma and Bio Sciences, 2014)
Pre-eclampsia (PE) is a unique syndrome in human pregnancy. To assess the effect of coalesce strategies on PE, a randomized clinical trial on 240 at risk primigravid mothers, by proportionate stratified random sampling was conducted. Mothers were stratified as Group A-age < 18 years, Group –B age > 30 years & Group C mothers BMI ≥30kgm2-obese).Coalecse strategies (Increased dose of calcium lactate supplementation from 300 mg to 1500 and stretching exercises) were given to the study group from 17 weeks of gestation till the end of pregnancy. Subjects were assessed for SBP, DBP, and proteinuria at scheduled visits in both the groups.Maternal, fetal and neonatal outcome were assessed at the end of the delivery. Results showed that 17 out of 108 mothers in the study and 31 out of 103 mothers in control group developed PE at the end of pregnancy at p≤0.001 level (t=4582.50, p=0.003**). Study concludes that coalesce strategies were found effective in the prevention of PE and confers a favorable maternal, fetal, and neonatal outcome.